Biocheese: A Food Probiotic Carrier. (23rd February 2015) - Castro, J. M.; Tornadijo, M. E.; Fresno, J. M.; Sandoval, H.
Abstract : This review describes some aspects related to the technological barriers encountered in the development and stability of probiotic cheeses. Aspects concerning the viability of probiotic cultures in this matrix are discussed and the potential of cheese as a biofunctional food carrier is analyzed, outlying some points related to health and safety. In general, the manufacture of probiotic cheese should have little change when compared with the elaboration of cheese in the traditional way. The physicochemical and technological parameters influencing the quality of these products have also to be measured so as to obtain a process optimization.